Optical sectioning in multi-foci Raman hyperspectral imaging - Liao, Zhiyu; Sinjab, Faris; Elsheikha, Hany M.; Notingher, Ioan (Wiley, 2018)
In this study, we compared the depth-discrimination and speed performance of multi-foci Raman hyperspectral imaging with the reference standard of a single laser point confocal Raman mapping. A liquid crystal spatial light modulator (LC-SLM) was employed for the generation of multi-foci laser beams, and a digital micromirror device (DMD) was used as a software-configurable reflective pinhole array. The patterns of the laser-foci and pinhole array can be rapidly changed without requiring any hardware alterations. Confocal patterns with different distance-to-size ratios were tested and compared. After optimisation of the laser foci pattern, we demonstrated the feasibility of multi-foci Raman hyperspectral microscopy for recording depth-resolved molecular maps of biological cells (Acanthamoeba castellanii trophozoites). Micrometric depth-discrimination and short acquisition times (20 minutes for single plane confocal image) was achieved.